2022
DOI: 10.1021/acs.jpclett.2c01080
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Structural Insights into Phospholipid Transfer from Membranes with Different Curvatures by Time-Resolved Neutron Scattering

Abstract: Understanding how lipid dynamics change with membrane curvature is important given that biological membranes constantly change their curvature and morphology through membrane fusion and endo-/exocytosis. Here, we used time-resolved small-angle neutron scattering and time-resolved fluorescence to characterize the properties and dynamics of phospholipids in vesicles with different curvatures. Dissociation of phospholipids from vesicles required traversing an energy barrier comprising positive enthalpy and negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…SANS was also used to evaluate the transition of lipid nanodisks to unilamellar vesicles [ 243 ]. Simple curvature effects can facilitate lipid exchange [ 244 ], for example, and so can methanol [ 245 ]. The transport of cholesterol between POPC vesicles and between leaflets of a single vesicle was found by SANS to be slower than previously reported [ 246 ].…”
Section: Examplesmentioning
confidence: 99%
“…SANS was also used to evaluate the transition of lipid nanodisks to unilamellar vesicles [ 243 ]. Simple curvature effects can facilitate lipid exchange [ 244 ], for example, and so can methanol [ 245 ]. The transport of cholesterol between POPC vesicles and between leaflets of a single vesicle was found by SANS to be slower than previously reported [ 246 ].…”
Section: Examplesmentioning
confidence: 99%
“…Lipid exchange between vesicles reduces the SLD difference, i.e., contrast, and decreases scattering from the vesicles (Figure B). We found that the spontaneous transfer of POPCs between vesicles is very slow (Figure C), which is consistent with previous results. , The addition of PEG8000 or PEG20000 immediately decreased the contrast, suggesting enhanced lipid exchange. On the contrary, the enhancement effect of PEG200 was remarkably smaller, indicating that lipid exchange is induced by vesicle aggregation.…”
mentioning
confidence: 99%
“…The values of Δ H ⧧ and − T Δ S ⧧ were positive and negative, respectively (Figure C), indicating that PEG-mediated lipid transfer is an enthalpically unfavorable but slightly entropically favorable process. Compared to the parameters without PEG, the changes in the activation free energy, enthalpy, and entropy upon the addition of PEG [Δ(Δ G ⧧ ), Δ(Δ H ⧧ ), and Δ(− T Δ S ⧧ )] were −12.2, 5.2, and −17.4 kJ/mol at 37 °C, respectively (Figure C). Thus, the decrease in the activation free energy was due to the increase in activation entropy, which is discussed below.…”
mentioning
confidence: 99%
See 2 more Smart Citations